2019
DOI: 10.1177/0049475519855294
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the resumption of sexual intercourse before the scheduled six-week postpartum visit

Abstract: This retrospective cohort study was aimed at evaluating the factors associated with the resumption of sexual intercourse (SI) before the six-week postpartum visit and was carried out between 1 January and 15 February 2014. The main variables studied included maternal age, number of living children, mode of delivery, complications observed at delivery and resumption or not of SI. Data from women who resumed SI were compared to those of women who did not. Fisher’s exact test and t-test were used for comparison. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Wanting another child within six months postdelivery seems too early although not surprising; as a prior study conducted in Uganda in 2014 (about the same time when these data were collected) registered high fertility desires and pregnancy intentions among women living with HIV [30]. Similar studies in Cameroon and Ethiopia which evaluated factors associated with sexual intercourse resumption before the 6-week postpartum visit [10,50] also found among other factors that, having one child, was signi cantly associated with sexual intercourse resumption [51]. In Ethiopia, a cross-sectional study among postnatal women similarly found among other factors, that desire for another child coupled with pressure from the husband to initiate sexual intercourse, were signi cantly associated with early sex resumption [50].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Wanting another child within six months postdelivery seems too early although not surprising; as a prior study conducted in Uganda in 2014 (about the same time when these data were collected) registered high fertility desires and pregnancy intentions among women living with HIV [30]. Similar studies in Cameroon and Ethiopia which evaluated factors associated with sexual intercourse resumption before the 6-week postpartum visit [10,50] also found among other factors that, having one child, was signi cantly associated with sexual intercourse resumption [51]. In Ethiopia, a cross-sectional study among postnatal women similarly found among other factors, that desire for another child coupled with pressure from the husband to initiate sexual intercourse, were signi cantly associated with early sex resumption [50].…”
Section: Discussionmentioning
confidence: 82%
“…The women had 3 options to choose from: 1) within 6 weeks; 2) after 6 weeks; 3) I don't remember. Those who chose the third option were assumed to have resumed sexual intercourse within 6 weeks based on ndings from a prior study where 68% of postnatal women who resumed sexual intercourse within 6 weeks did not attend their scheduled six-week postnatal clinic visit [10,45].…”
Section: Study Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to the World Health WHO and other studies, more than half (50%), of women resume sexual activity within 6 weeks of childbirth ( 9 – 11 ). For instance, in Turkey 79.1% and China 68.7% of postpartum women engage sexual activity within the first 6 weeks of childbirth ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the factors found to affect the quality of life of postpartum women include depression, lactation problems, urinary complications and di culties engaging in sexual intercourse after child birth [7]. Although several studies have in the recent past explored issues around sexuality during the postnatal period, the majority focussed on women in the general population as opposed to those living with HIV [8][9][10][11]. Women living with HIV require special attention as they experience unique challenges with their health-related quality of life which are exacerbated by a compromised immunity [12].…”
Section: Introductionmentioning
confidence: 99%